ECONOMIC VALUE AND POTENTIAL FOR TOURISM DEVELOPMENT OF TWAL POMBO ISLAND, SALAHUTU, CENTRAL MALUKU, MALUKU - Kesya Pattimukay (Pusbindiklat - LIPI, 2015)
Small island region has the potential of natural resources and high environmental services and can serve as the basis for implementing the capital of Indonesia’s development in the future. This area provides a productive resource such as coral reef, seagrass, mangrove forests, fisheries, and conservation areas. TWAL Pombo Island is a nature conservation area used for tourism and outdoor recreation. Some of the factors that inhibit Pombo Island tourism development areas such as; the lack of local government partisanship the management of the island, defense and safety, lack of basic infrastructure, and environmental degradation. The development of tourism in the region needs to be done as foreign exchange earnings for the region given the island’s natural beauty, andthe location is very strategic because it is more easily reached from the city center. Based on those factors, this study aims to identification of Pombo Island tourism potential based on the preception of tourists, estimates of the economic value that can be generated from the tourist island of Pombo, policy formulation development potential as a tourist attraction in the region Pombo Island.